GRAMMATICAL INTRICACY DALAM CERITA PENDEK KARYA PENULIS ANAK INDONESIA - Izzati, Novia (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2019)
This paper aims to describe the grammatical intricacy of short story written by an Indonesian child author. Grammatical intricacy is built of clause, nominal group, and lexis. These three aspects show us how the author expresses his mind into language. The data source is short story titled “Mahkota Surga untuk Ayah”. The author is an Indonesian child whose her story has been published by Lintang. This research is a kind of descriptive qualitative using observation-notification technique (simak-catat). The data are clauses, nominal groups, and lexis of the text. The result shows that the author exploited the language in 148 clauses and most of them are complex clauses. The thing goes different for nominal groups, most of them are in simplex. Most of lexis are exploited in congruent forms. From the characteristics of the language author used this text is written in spoken language and has a high grammatical intricacy.